Our Place / Infanzah Qistina Irwansyah...[et al.] - Irwansyah, Infanzah Qistina; Pg Johari, Syaizatul Shafiqah; Jaafar, Mohamad Farhan; Ahmad, Muhamed Faiz (2014)
The business is based on a partnership consists of 4 members. We have General Manager, Marketing Manager, Operational Manager, Financial Manager, and hiring Administrative Manager. We obtain our business capital majority from a loan from CIMB Bank and capital contribution from each of our manager, costing up to RM 200,000. We intend to set up business serviced-based with a name Our Place. We agreed to set up our business and commence it on 1st April 2014 at LOT 1-25, First Floor, Suria Sabah, JalanTunFuad Stephen, Kota Kinabalu, Sabah. Our business is mainly about giving the social space for the customers to relax and feel comfort plus having some fun. As many tougher competitions we would face in running our business, we include a special value in our service that is gives customer's need and wants at the same time achieved the targeted profit. We are mainly focused on customer's satisfaction and followed by the long term profits to do the business. Our marketing strategy is very important in purpose to diversify the business ideas and In order to determine business successful. Since our business was started from scratch, therefore we have to come up with ideas on how we can attract people interest and make a lot of profit. Besides that, financial management is important as a guideline for our company in order to start a fresh business. From the financial plan we can plan to minimize the expenses and maximize the profit in our business. It includes the entire of financial pan for department. It also shows the short and long-term financial and also the amount of capital that we need for this business which is by loan and cash contribution from the partners.